Rent [videorecording (DVD)] - Columbus, Chris; Rapp, Anthony; Pascal, Adam; Dawson, Rosario; Martin, Jesse L.; Menzel, Idina; Diggs, Taye; Larson, Jonathan (Sony Pictures Home Entertainment, 2006)
Focuses on the year in the life of a group of friends in New York's East Village. The "bohemians" live carefree lives of art, music, sex, and drugs. It is carefree until Mark, an aspiring filmmaker, and Roger, an aspiring songwriter, find out they owe a year's rent to Benny. Benny is a former friend who had promised them free rent when he married the landlord's daughter. Roger has also attracted the attention of his downstairs neighbor, Mimi. Mark's former girlfriend, Maureen, has found a new romance in a lawyer named Joanne. Philosophy professor Tom finds his soul mate in drag queen Angel. With this being the late 1980s, the threat of AIDS is always present.